VHDL Design and FPGA Implementation of a High Data Rate Turbo Decoder based on Majority Logic Codes - A. Boudaoud; M. El Haroussi; E. Abdelmounim (Institute of Advanced Engineering and Science, 2017)
This paper presents the electronic synthesis, VHDL design and implementation on FPGA of turbo decoders for Difference Set Codes (DSC) decoded by the majority logic (ML). The VHDL design is based on the decoding equations that we have simplified, in order to reduce the complexity and is implemented on parallel process to increase the data rate. A co-simulation using the Dsp-Builder tool on a platform designed on Matlab/Simulink, allows the measurement of the performance in terms of BER (Bit Error Rate) as well as the decoder validation. These decoders can be a good choice for future digital transmission chains. For example, for the Turbo decoder based on the product code DSC (21.11)² with a quantization of 5 bits and for one complete iteration, the results show the possibility of integration of our entire turbo decoder on a single chip, with lower latency at 0.23 microseconds and data rate greater than 500 Mb/s.